PENGOLAHAN GULA SEMUT AREN PADA MASYARAKAT DESA CISIMEUT RAYA KECAMATAN LEUWIDAMAR - Ahmad Sudadi; Bambang Setyo Panulisan; Annisa Novia Nuha Nafisa; Firda Nurwulan; Muhammad Vidiansyah; Yosep Firdaus; Eva Juliantina; Oktaviar Rahman Putra (STAI Darul Qalam Tangerang, 2022)
Sugar palm (Arenga pinata) is one of the plants cultivated by the people of Cisimeut Raya Village, Leuwidamar District. There are about 200 palm trees scattered in this area. So far, palm sap is sold by farmers to a place for printing palm sugar manufacturing. Ant sugar is one of the processed products of palm sap in the form of crystals which has a higher price than printed palm sugar. The purpose of this Student Work & Community Service Lecture is so that the people of Cisimeut Raya have the knowledge and skills to process palm sap into ant sugar. The target of this activity is the women's farmer group in the Cisimeut Raya area. The activity is carried out in the form of training and demonstrations of making ant sugar. The activity runs smoothly and the women's farmer group has made ant sugar independently and sells its products to consumers